Prognostic Factors in Extremity Soft Tissue Sarcoma Patients Treated with Preoperative Radiotherapy - Inanc, MD, Berrin; Inanc, MD, Kubilay (International Journal of Innovative Research in Medical Science, 2019)
Purpose: The purpose of the study was to investigate the prognostic factors and survival after preoperative radiotherapy in Extremity Soft Tissue Sarcomas (ESTS). Materials and Methods: In this retrospective study, all patients treated for an extremity sarcoma with pre-operative radiotherapy followed by surgery. Results: The mean follow-up for all 24 ESTS patients was 15.5 (range: 10-39 months). At last follow-up, 9 patients (37%) were alive, 15 patients (62%) had died of distant disease progression. Among the patients died, there were 15 with metastatic relapse (13 lung and 2 cranial metastasis), 5 with both local and metastatic recurrence. The median OS was 16 month. The 2-years actuarial OS rate and 3-years OS rate were 39% and 26%, respectively. The median RFS was 14(12.5-15.4) month. The 2-years and 3-years RFS rate was 71%.The median MFS was 12 months. The 2-years and 3-years MFS rate were 33%, 17%, respectively. The effects of age, sex, histopathologic type, tumor size, tumor localization, tumor grade, tumor depth, radiation doses and recestion margin on OS, RFS, MFS were not observed. In univariate and multivariate model, it was observed that recurrence decreased OS time significantly (p<0.05). Conclusion: Recurrens and metastasis are strong and negative prognostic factor for survival in extremity soft tissue sarcoma patients.